THE REASONS AND FACTORS OF DE-CENTRALIZATION OF RUSSIAN ISLAM IN POST-SOVIET PERIOD - Dzhabrail Gasanovich Mirzakhanov (Современная наука и инновации)
This paper is examine crucial trends and aspects of fragmentation of modern Russian Muslim society. The main aim is analysis of processes of cleavage and successive de-centralization Russian Islam in post-Soviet. This evolution exceed the limits of historically regional partition of Russian Islam community to key areas: North Caucasus and Volga-Ural a new phenomenon in modern Russian policy. The author argues that this processes have a political characteristics and is a part of post-Soviet Russian political transformation.